Relationship Ending in the Concept of Customer Relationship Management - Hajduk-Kasprowicz, Ewa; Nieżurawski, Lech (Olsztyn Economic Journal, 2015)
The paper discusses the problems of fading and ending of business relationships in the sphere of professional services i.e. the phase of a relationship dissolution resulting from a client's or a firm's decision to end it. This phase includes, among others, determining the causes of the relationship dissolution and drawing conclusions for the future in order to prevent losing the most lucrative clients. Both in theory and in practice, relationship ending is perceived as something stretched in time i.e. consisting of numerous stages and influenced by numerous factors and events.The aim of the present paper is an analysis of the modern literature on the causes and mechanisms of business relationships termination in the sphere of professional services as well as indicating some possibilities of a more effective and efficient management of these relations.